ANALISIS PENGARUH DISIPLIN KERJA DAN KOMITMEN PEGAWAI TERHADAP KINERJA PEGAWAI PADA PT. JASA MARGA (PERSERO) CABANG SURABAYA - GEMPOL - Sutomo Sutomo (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
Analysis of the Influence of Work Discipline with Employee Commitment to Employee Performance at PT. Jasa Marga Branch Surabaya-Gempol. This study analyzed various factors that can affect employee performance at PT. Jasa Marga Branch Surabaya-Gempol (Y). The purpose of the research is to look at the simultaneous influence of work discipline and employee commitment to employee performance at PT. Jasa Marga Surabaya-Gempol Branch, To see the influence of work discipline with partial employee commitment to employee performance, and to know the real influence of each discipline of work factors with employee commitment to the performance of company employees. The population is employees in PT. Jasa Marga Surabaya Branch - Gempol as many as 30 people. The sample was determined from 100% of the total population; therefore, the sample in this study was 30 employees, where the determination was through the technique of total sampling (saturated sampling). This study uses a model of analysis of multiple linear regression data. The model was chosen because it wants to see the significant influence of independent variables on employee performance simultaneously or partially. Conclusions in this study include: (1) factors of recognition of work, performance, work itself, awards and responsibilities simultaneously affect the performance of employees at PT. Jasa Marga Branch Surabaya-Gempol (Y), (2) All factors of work discipline, employee commitment and education level partially affect employee performance in the company, (3) The dominant influencing of employee performance in this company is leadership with a partial influence of 39.9%.